Enhanced phycocyanin production from Spirulina subsalsa via freshwater and marine cultivation with optimized light source and temperature. (June 2023) - Jiang, Liqun; Yu, Siteng; Chen, Huiying; Pei, Haiyan
Graphical abstract: Highlights: Phycocyanin produced by S. subsalsa in freshwater and marine media were evaluated. S. subsalsa differently responded to light and temperature in the two media. A two-stage strategy timely involving 35 °C and green light was proposed and applied. Growth negatively relates to phycocyanin/chlorophyll ratio except temperature test. Abstract: To find out optimum and cost-efficient strategy for phycocyanin production, the effect of light source and temperature on Spirulina subsalsa growth were studied in chemically defined freshwater medium and seawater supplied with wastewater from glutamic acid fermentation tank. Maximum growth rate and the highest phycocyanin content were obtained by 35 °C and green light, respectively. A two-stage cultivation strategy was proposed and applied, which combines biomass accumulation at 35 °C and phycocyanin synthesis simulated under green light. As a result, phycocyanin production reached 70 mg/L/d and 11 mg/L/d from freshwater and seawater medium, respectively. With all tested conditions, a strong correlation between biomass and phycocyanin/chlorophyll ratio, rather than phycocyanin, revealed the dependence of Spirulina subsalsa growth on coordinating regulation of photosynthetic pigments. The relationship between growth and phycocyanin production under various light and temperature can be a good basis for improving phycocyanin production from Spirulina subsalsa with or without freshwater consumption.